2020
DOI: 10.3390/cancers12061537
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Ficlatuzumab and Cetuximab in Cetuximab-Resistant, Recurrent/Metastatic Head and Neck Cancer

Abstract: Cetuximab, an anti-EGFR monoclonal antibody (mAb), is approved for advanced head and neck squamous cell carcinoma (HNSCC) but benefits a minority. An established tumor-intrinsic resistance mechanism is cross-talk between the EGFR and hepatocyte growth factor (HGF)/cMet pathways. Dual pathway inhibition may overcome cetuximab resistance. This Phase I study evaluated the combination of cetuximab and ficlatuzumab, an anti-HGF mAb, in patients with recurrent/metastatic HNSCC. The primary objective was to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…c-Met seems to be a promising biomarker for prognosis in OPSCC and an attractive objective for targeted therapy. Phase 2 trial of humanized monoclonal anti c-Met antibody ficlatuzumab with or without cetuximab in cetuximab resistant recurrent or metastatic HNSCC may be able to show possible effects NCT03422536) [ 74 ]. Unfortunately, the combination of tivantinib (anti c-Met tyrosine kinase inhibitor) and cetuximab was not found to improve the response rate and survival [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…c-Met seems to be a promising biomarker for prognosis in OPSCC and an attractive objective for targeted therapy. Phase 2 trial of humanized monoclonal anti c-Met antibody ficlatuzumab with or without cetuximab in cetuximab resistant recurrent or metastatic HNSCC may be able to show possible effects NCT03422536) [ 74 ]. Unfortunately, the combination of tivantinib (anti c-Met tyrosine kinase inhibitor) and cetuximab was not found to improve the response rate and survival [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bauman et al investigated changes in immune signatures in a phase I study of an anti-HGF antibody and an anti-EGFR antibody in patients with cetuximab-resistant, recurrent/ metastatic squamous cell carcinoma. An increase in peripheral T cells, particularly a CD8 + subset, was associated with treatment response (Bauman et al, 2020). Mukherjee et al identified CCL5 as a poor prognostic blood biomarker associated with lower overall survival in patients with advanced pancreatic cancer treated with anti-PD-1.…”
Section: Fsfc Contributions To Cancer Immunotherapy Researchmentioning
confidence: 99%
“…Near limitless throughput and high capture efficiency paired with the ability to distinguish rare cell populations provides a powerful tool for immunophenotyping. Indeed, FSFC has been successfully applied to identify therapy-mediated alterations in peripheral blood mononucleocyte profiles of head and neck squamous cell carcinoma patients ( 252 ).…”
Section: Single-cell Multi-omics Platforms and Their Prospect In Gene And Cell Therapymentioning
confidence: 99%